Propagación in vivo de cinchona officinalis L., a partir de material vegetal sexual y asexual, con fines de conservación de la especie - Conde Montaño, Marco Elí (2016)
The province Loja is possessor of a great diversity of sorts, as the case of the kind is Cinchona, per se that the object has been of an exploitation without foresights for the future (Anda, 2002). Cinchona Officinalis L, it is a forestal sort that comes disappearing at our national territory for many reasons: Deforestation, illegal felling of trees, migrant agriculture, periodic burnings, etc., (Acosta 1980). Present it investigation developed within the project's frame “Identification and description of the present-day status of Cinchona officinalis L., at the province of Loja and generation of protocols for propagation alive in and in vitro”, in two phases; Phase of field and phase of greenhouse; Inside the period understood between May 2015 – January 2016. The phase of field corresponded to the anthology of vegetable material at the sectors: Narrow pass of the Naque (Loja), Quebrada St. Simón (Loja), parish church the Tambo I lay siege to Uritusinga (Catamayo) and parish church Selva Make Happy (Saraguro), and second phase carried completion at the greenhouse of Loja's National University itself. In the phase of greenhouse with the purpose to improve the propagation alive in of the forestal sort Cinchona officinalis L, they practiced several techniques of sexual and asexual propagation. Two controls tasted three further types of substratums themselves for the sexual propagation for seeds: Substratum land, sand and disturb in proportions 1:1:1; 2:1:1 and 1:1:2 plus the witnesses disturbs (100 %) and land (100 %). They sold off the following essays for the asexual propagation: a) I rehearse of enraizamiento of stakes, where the effect of two commercial hormones was tried: Hormonagro 1 and Enraizador H.V; b) I rehearse of enraizamiento of sprouts, where the effect of two commercial hormones was tried: Hormonagro 1 and Enraizador H.V; and c) I rehearse of enraizamiento of aerial layers, where three types of substratums were tried: Organic land, moss sphagnun and sawdust. As a result it was obtained than the germination of seeds in Cinchona officinalis L, the highest percentage of germination corresponds to the treatment T3 (1:1:2) and T4 (the witness disturbs) with a 71.67 % and 83.33 %, the T5 presented a 20 %'s relatively low percentage (witness land); the T1 (1:1:1) and T2 (2:1:1) you presented a 46.67 %'s percentage; And 43.33 % respectively. The essays of asexual propagation in Cinchona officinalis L: Hormones the commercial enraizantes (Hormonagro 1 and Enraizador H.V) did not have a positive effect in the enraizamiento of stakes, so that it relates to the enraizamiento of sprouts they answered the vegetative propagation favorably in the three treatments: T1 (Without Hormonagro), T2 (powdered Hormonagro) and T3 (Hormonagro in liquid). Referring to enraizamiento's percentage and number of roots in the sprouts did not have significant differences between treatments; The treatment T3 (Hormonagro in liquid) was the best treatment in regards to the length of in-bud roots (3.23 cm); The substratum fixed by organic land went the that you presented better results in the enraizamiento of aerial layers in Cinchona officinalis L, because it attained enraizamiento's percentage of the 50 % unlike the other substratums. Promising data for the future utilization of the same in essays of sexual and asexual propagation of forestal sorts perteneciente to the family Rubiaceae.